THE NEXUS BETWEEN GENERAL COGNITIVE ABILITY OF IMAMSHIP AND MASJID PERFORMANCE: A MEDIATING QUANTITATIVE PERSPECTIVE - Abdulhadi Alade Tihamiyu Eniafe; Dr. Adi Anuar bin Azmin @ Che Wan; Prof. Madya. Dr. Shuhairimi (Journal of Islamic, Social, Economics and Development, 2021)
This study aims to formulate the mediating effect of Islamic Ethical AdministrativePractice (IEAP) on the nexus (relationship) between general cognitive ability (GCA) ofImamship (leadership in Islam) and Masjid performance (MP) of the Islamic community(Muslim Ummah) in Lagos State, Nigeria. This study is quantitative using a cross-sectionalsurvey questionnaire, and statistical techniques to analyze the collected data with partial leastsquare structural - equation modelling - version 3 (PLS-SEM-V3). The determinants of IEAPinclude four dimensions which are: (a) Competition, (b) Effort, (c) Morally ResponsibleBehaviour, and (d) Transparency. The GCA of Imamship factors are (a) Knowledge/Wisdom,(b) Truthfulness, (c) Responsibility/Trust, and (d) Deliverance of Khutbah. While the MP ismeasured with three dimensions: (a) Masjid Attendance, (b) Masjid Activities, and (c) MasjidFunding. The researcher sampled 310 Chief Imams of Central Masaajid (mosques) asrespondents in Lagos State of Nigeria. The findings showed that all the IEAP factors had asignificant positive relationship with GCA of Imamship and MP. The results of the studyprovide some insights into the Imamship of Masaajid in Lagos State, Nigeria in particular, andall other Masaajid in the country in general.